The Workers' Educational Association: A Study in Social Change and Resistance in Canadian Working Class Culture. - Benjamin, Amanda (Concordia University, 1999)
This thesis examines the effects of the Workers' Educational Association of Toronto (WEA) on social change in Canada between 1917-1945. This study attempts to establish the social importance of this organization in the history of adult education in Canada. The WEA was an educational organization that attempted to provide a link between labour and learning by making educational opportunities available to the working class. The data for this study were obtained from an analysis of the Ontario and Canadian WEA archives. The thesis first examines the history of the WEA and demonstrate its place in the history of adult education in Canada. Secondly, this study suggests that the WEA was the impetus for change in Canada, and in particular for Toronto's working class. The study found that the WEA used a form of critical pedagogy to achieve its goals which brought about social change. This study reinforces the usefulness of critical pedagogy as an approach for adult education when social change is an objective.